Consumer perception of agricultural products in Nandayure, Guanacaste, Costa Rica - Sánchez Brenes, Ronald (2024)
One factor contributing to food and nutritional security is knowing consumers’ perceptions of agricultural products. This research aims to determine consumer perception to enhance the dynamics of short agricultural chains in Nandayure, Costa Rica. A survey was conducted among 300 consumers of agricultural products for the 2021-2022 period. The instrument was divided into three sections: demographic and socioeconomic aspects, purchasing behavior, and agricultural consumer products. Results show that among respondents, women purchase more than men, are between the ages of 21 and 40, and invest less than ₡20,000 a week. Shopping is done once a week at produce markets and supermarkets that must be organized and clean and offer information and different payment methods. The most important characteristics consumers prioritize in products are freshness, quality, and price. The main types of products consumed were fruits 38%, vegetables 23%, and medicinal and aromatic plants 18%. Understanding local marketing dynamics allows for the analysis or interpretation of short-chain models and consumer trends influencing the availability and acquisition of agricultural products. This could generate opportunities to develop market niches focused on high-quality products with added value and strategic alliances with public and private entities.